2015
DOI: 10.3389/fmicb.2015.00198
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of plant growth-promoting rhizobacteria from wheat rhizosphere and their effect on plant growth promotion

Abstract: The present study was conducted to characterize the native plant growth promoting (PGP) bacteria from wheat rhizosphere and root-endosphere in the Himalayan region of Rawalakot, Azad Jammu and Kashmir (AJK), Pakistan. Nine bacterial isolates were purified, screened in vitro for PGP characteristics and evaluated for their beneficial effects on the early growth of wheat (Triticum aestivum L.). Among nine bacterial isolates, seven were able to produce indole-3- acetic acid in tryptophan-supplemented medium; seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
216
1
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(252 citation statements)
references
References 44 publications
(49 reference statements)
26
216
1
9
Order By: Relevance
“…Similarly, Shaharoona et al reported that N use efficiency increased in response to inoculation with Pseudomonas fluorescens at all fertilizer levels in wheat [167]. PGPR isolates significantly increased shoot and root length, shoot and root dry weight, grain weight per spike, shoot and root N content and also enhanced the N contents of inoculated wheat seedlings [168]. Barneix et al reported that inoculation of wheat with Bacillus simplex and Bacillus firmis resulted in consistent increase in dry matter and wheat grain quality.…”
Section: Improve Yield and Quality Of Wheatmentioning
confidence: 99%
“…Similarly, Shaharoona et al reported that N use efficiency increased in response to inoculation with Pseudomonas fluorescens at all fertilizer levels in wheat [167]. PGPR isolates significantly increased shoot and root length, shoot and root dry weight, grain weight per spike, shoot and root N content and also enhanced the N contents of inoculated wheat seedlings [168]. Barneix et al reported that inoculation of wheat with Bacillus simplex and Bacillus firmis resulted in consistent increase in dry matter and wheat grain quality.…”
Section: Improve Yield and Quality Of Wheatmentioning
confidence: 99%
“…The components released by A. brasilense responsible for stimulating root growth are indole-acetic acid (IAA), gibberellins, and cytokinins (Tien et al, 1979). The increase in root development caused by inoculation with Azospirillum is involved with several other effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several PGPB genera are being studied because of their ability to establish associations with economically attractive grasses, such as sorghum, rice, sugarcane and wheat (Idris et al, 2009;Pedrosa et al, 2011;Majeed et al, 2015). For maize, the results of plant growth promotion with PGPB inoculation of the genera Herbaspirillum and Azospirillium, are well documented, being the latter with registration in the Ministry of Livestock Farming and Supply for use in commercial formulations (Hungria et al, 2010).…”
Section: Introductionmentioning
confidence: 99%